Influence of Advertising and Sales Promotion on Buying Decision - Kurniawan, Teuku Reza (Adpebi International Journal of Multidisciplinary Sciences, 2023)
Purpose –The purpose of this study was to determine the effect of advertising and sales promotion on Buying decisions for the president brand luggage at the Pekanbaru Transmart Mall.Methodology/approaches – Source of data obtained from primary and secondary data. the total population is 520 consumers, while the total sample is 84 consumers, the sampling technique is incidental sampling. Data analysis was descriptive and quantitative (in the form of classic assumption tests and hypothesis testing.Findings –The results showed that both the partial and simultaneous tests of all independent variables had a significant effect on the dependent variable. And the magnitude of the influence of the independent variable on the dependent variable is 36.40 percent while the remaining 63.60 percent is influenced by other variables outside the research. Novelty/values –Qhat the factors that influence purchasing decisions are sales promotions and advertising.